2021
DOI: 10.1039/d0ra09197a
|View full text |Cite
|
Sign up to set email alerts
|

Practical aspects of electrophoretic deposition to produce commercially viable supercapacitor energy storage electrodes

Abstract: Electrophoretic deposition (EPD) is a highly convenient and demonstrated industrial operation for coatings manufacture. It is now suitable for the production of practical energy storage electrodes for batteries, capacitors & solid-state devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…In comparison, a recent work by WMG provides much better mass loadings and film thicknesses, as can be gleaned from Tables 5 and 6 246 . Therefore, a versatile EPD method has been established in WMG for preparing high‐performance supercapacitors that meet the industrial standards for good mass loadings and film thicknesses as shown in Figure 15 248 . The EPD conditions used for the study in question were very similar for producing high mass loadings (and decent coating thicknesses) for SiO 2 separators for LiB applications (shown as an example only in Table 6).…”
Section: Research Discovery and Innovation Activities On Epd For Ees ...mentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison, a recent work by WMG provides much better mass loadings and film thicknesses, as can be gleaned from Tables 5 and 6 246 . Therefore, a versatile EPD method has been established in WMG for preparing high‐performance supercapacitors that meet the industrial standards for good mass loadings and film thicknesses as shown in Figure 15 248 . The EPD conditions used for the study in question were very similar for producing high mass loadings (and decent coating thicknesses) for SiO 2 separators for LiB applications (shown as an example only in Table 6).…”
Section: Research Discovery and Innovation Activities On Epd For Ees ...mentioning
confidence: 99%
“…These electrodes were tested in both coin cell and A7 pouch cell supercapacitors and gave very good performance—excellent capacitance retention is noted for both cells at 0.1 A g −1 current density. Reproduced with permission from RSC 248 …”
Section: Research Discovery and Innovation Activities On Epd For Ees ...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is receiving a high level of attention in academia, as well as by industry communities in many patents publications, as a modern tool to produce components of electrochemical energy devices. Many examples are recorded in the literature: 1) Energy storage electrodes in lithium-ion battery, [1][2][3][4] supercapacitor [5] and flow battery [6] 2) Solid-state electrolytes in solid oxide fuel cell [7] 3) Membrane electrode assembly in proton exchange fuel cell [8] 4) Photovoltaic electrodes in dye-sensitized solar cell [9] 5) Hydrogen production electrodes in water electrolyser [10] 6) Membrane separator in lithium-ion battery [11] 7) Ceramic-in-polymer electrolyte for lithium-ion battery [12] 8) Porous electrodes in structural lithium-ion battery [13] For lithium-ion batteries, half-cell activities with small-area EPD electrodes have thus far been the focus for fundamental studies. The EPD electrode design have provided useful electronic, ionic and interfacial charge transports in lithium-ion battery applications.…”
Section: Introductionmentioning
confidence: 99%
“… Energy storage electrodes in lithium‐ion battery, [1–4] supercapacitor [5] and flow battery [6] Solid‐state electrolytes in solid oxide fuel cell [7] Membrane electrode assembly in proton exchange fuel cell [8] Photovoltaic electrodes in dye‐sensitized solar cell [9] Hydrogen production electrodes in water electrolyser [10] Membrane separator in lithium‐ion battery [11] Ceramic‐in‐polymer electrolyte for lithium‐ion battery [12] Porous electrodes in structural lithium‐ion battery [13] …”
Section: Introductionmentioning
confidence: 99%